The Potential of Complementary Therapy Using Bay Leaves (Syzygium polyanthum) and Ginger (Zingiber officinale) in Lowering Blood Glucose Levels in Patients with Diabetes Mellitus: A Literature Review - Ria Rizka Mansur; Musdalipa Musdalipa; Selviana Tawil (Lembaga Pengembangan Kinerja Dosen, 2025)
Diabetes mellitus (DM) is a global public health issue, with its prevalence steadily increasing. The 2023 Indonesian Health Survey (SKI) reported that 11.7% of the population aged ≥15 years is affected by DM. DM is marked by high blood glucose levels due to impaired insulin secretion or action, leading to chronic complications. While conventional treatments such as insulin and oral antidiabetic drugs are effective, their long-term use can cause side effects, including hypoglycemia, gastrointestinal issues, and economic burdens. As a result, herbal-based complementary therapies are gaining attention due to their safety, accessibility, and alignment with Indonesian culture. Research suggests that certain herbs can lower blood glucose by increasing insulin secretion, improving insulin sensitivity, inhibiting glucose absorption, and offering antioxidant effects. Herbs like bay leaves (Syzygium polyanthum) and ginger (Zingiber officinale) have shown hypoglycemic activity. This literature review aims to explore the potential, mechanisms, preparation, and clinical evidence of using bay leaves and ginger for glycemic control. Findings indicate that both herbs improve insulin sensitivity, inhibit α-glucosidase, and exhibit antioxidant effects. However, further research, including large-scale clinical trials and multidisciplinary studies, is needed to validate these benefits and explore synergies with conventional therapies.